2012
DOI: 10.1097/mnm.0b013e32834eaca1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the postoperative pulmonary function in lung cancer patients with borderline function using ventilation–perfusion scintigraphy

Abstract: Ventilation-perfusion scans can predict postoperative pulmonary function and help evaluate the risk of surgery for lung cancer patients with borderline pulmonary functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Prediction of postoperative lung function in patients undergoing pulmonary resection is an important factor that may determine the feasibility of the surgery. There have been reports of the usefulness of lung perfusion scintigraphy in predicting postoperative lung function (14,18,19). Tom Holvoet et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction of postoperative lung function in patients undergoing pulmonary resection is an important factor that may determine the feasibility of the surgery. There have been reports of the usefulness of lung perfusion scintigraphy in predicting postoperative lung function (14,18,19). Tom Holvoet et al.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of postoperative lung function in patients undergoing pulmonary resection is an important factor that may determine the feasibility of the surgery. There have been reports of the usefulness of lung perfusion scintigraphy in predicting postoperative lung function (14,18,19). Tom Holvoet et al investigated whether anatomical segmental methods could replace perfusion scintigraphy; they have reported that FEV1s obtained using lung perfusion scintigraphy and anatomic segment method are very similar (4).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a preoperative FEV1 >2 L and predicted postoperative FEV1 >800 mL are considered to be eligible for pneumonectomy (29). In patients with borderline pulmonary parameters (FEV1 <2 L), a quantitative perfusion scan should be performed (30). A predicted postoperative FEV1 or DLCO of <40% indicates an increased risk of perioperative complications (31).…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…The most common anatomic location for sleeve resections is the upper lobe (39)(40)(41). Sleeve lobectomy is oncologically Figure 1 Algorithm of operability for pneumonectomy (28,(30)(31)(32)(33). CPET, cardiopulmonary exercise testing; ppo, predicted postoperative; VO2 max, maximal oxygen consumption.…”
Section: Surgical Decision-making: Pneumonectomy Versus Sleeve Lobectomymentioning
confidence: 99%